Estudo químico, atividade antioxidante e fotoprotetora de Chamaecrista sp. e Senna splendida - Silva, Tainá Souza (2017)
The Fabaceae family presents approximately 30% of the total species present in Caatinga. Among the genera belonging to this family are Chamaecrista and Senna, of which anthraquinones, flavonoids, diterpenes, alkaloids, among others have already been isolated. Species of these genera present several popular uses and pharmacological activities reported in the literature, among which, the antioxidant activity stands out. In view of this, this work had the objective of increasing the knowledge about the genera Chamaecrista and Senna through the phytochemical study of Chamaecrista sp. and Senna splendida, isolating their chemical constituents, evaluating the possible antioxidant and photoprotective activities of the extracts and phases obtained by liquid-liquid partition and searching for substances that showed activity as natural pH indicators. For this, the following methodologies were used: liquid column chromatography, gas chromatography, mass spectrometry, 1H and 13C nuclear magnetic resonance, Follin-Ciocalteu determination of phenolic content, determination of total flavonoids, percentage reduction of Diphenyl-picrylhydrazine (DPPH) and visible ultraviolet (UV-Vis) spectroscopy. The phytochemical study of Chamaecrista sp. resulted in the isolation of five substances, ß-sitosterol, stigmasterol, emodin, vitexin and orientin, while the study of Senna splendida resulted in the isolation of five substances (acid 3-ß-acetiloxi-lup-20(29)-en-28-oic, justicidin, ß-sitosterol and stigmasterol glucosides, rubrofusarin and quinquangulin glucosides) and identificativon by GC-MS of twelve substances (dihydroactinodiolide, phytone, methoxsalen, metylhexacosane, heptacosane, octacosane, nonacosane, triacontane, hentriacontane, ß-sitosterol, 4,22-estigmastadien-3-one e sitostenone). Emodin, isolated of Chamaecrista sp., presented the property of indicating the acid and basic character of solutions and was applied in practical class as a natural indicator of pH for teaching students, showing positive results. In the determination of phenolics, flavonoids and flavones and evaluation of the antioxidant activity by DPPH, the ethyl acetate phase of Chamaecrista sp. showed better results in relation to other samples (229.7 ± 5.21 mg EAG / g sample, 8.73 ± 0.22 µg querc / mg sample and EC50 9.3 ± 0.23 µg / ML, respectively) and in the evaluation of the photoprotective activity, emodin showed the best sun protection factor (24, 25), followed by the ethyl acetate phase of S. splendida, wich presented the best SPF = 10.76) in relation to the other extracts and phases tested